Leptospirosis in Colombia. Isolation of Leptospira hardjo from beef cattle grazing tropical savannas - Aycardi B., Eduardo R.; Torres, Blanca; Guzmán Romero, Víctor Hugo; Cortés, M. (1980)
Following a serological evaluation on the prevalence of leptospiral serotypes in a beef cattle herd in Colombia, three leptospires were recovered from affected cows. The animals came from an extensive native savanna pasture where the disease is apparently masked by malnutrition. The isolations were made from cows with low antibody titers. One isolate was obtained from the kidney of a killed cow and the other two from urine samples. The three isolates were identified as Leptospira interrogans serovar hardjo